Age at onset, course of illness and response to psychotherapy in bipolar disorder: results from the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD). Issue 16 (10th April 2014) - Peters, A.; Sylvia, L. G.; da Silva Magalhães, P. V.; Miklowitz, D. J.; Frank, E.; Otto, M. W.; Hansen, N. S.; Dougherty, D. D.; Berk, M.; Nierenberg, A. A.; Deckersbach, T.
Abstract : Background: The course of bipolar disorder progressively worsens in some patients. Although responses to pharmacotherapy appear to diminish with greater chronicity, less is known about whether patients' prior courses of illness are related to responses to psychotherapy. Method: Embedded in the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) was a randomized controlled trial of psychotherapy for bipolar depression comparing the efficacy of intensive psychotherapy with collaborative care (a three-session psycho-educational intervention). We assessed whether the number of previous mood episodes, age of illness onset, and illness duration predicted or moderated the likelihood of recovery and time until recovery from a depressive episode in patients in the two treatments. Results: Independently of treatment condition, participants with one to nine prior depressive episodes were more likely to recover and had faster time to recovery than those with 20 or more prior depressive episodes. Participants with fewer than 20 prior manic episodes had faster time to recovery than those with 20 or more episodes. Longer illness duration predicted a longer time to recovery. Participants were more likely to recover in intensive psychotherapy than collaborative care if they had 10–20 prior episodes of depression [number needed to treat (NNT) = 2.0], but equally likely to respond to psychotherapy and collaborative care if they had one to nine (NNT = 32.0) or >20 (NNT = 9.0) depressive episodes. Conclusions: Number of previous mood episodes and illness duration are associated with the likelihood and speed of recovery among bipolar patients receiving psychosocial treatments for depression.